2009
DOI: 10.1007/s11168-010-9066-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Grammars

Abstract: Interaction Grammars are a grammatical formalism based on the notion of polarity. Polarities express the resource sensitivity of natural languages by modelling the distinction between saturated and unsaturated syntactic structures. Syntactic composition is represented as a chemical reaction guided by the saturation of polarities. It is expressed in a model-theoretic framework where grammars are constraint systems using the notion of tree description and parsing appears as a process of building tree description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For a complete presentation of the formalism, the reader is referred to Guillaume and Perrier (2009).…”
Section: Interaction Grammarsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a complete presentation of the formalism, the reader is referred to Guillaume and Perrier (2009).…”
Section: Interaction Grammarsmentioning
confidence: 99%
“…A parse tree (as defined in Section 2.1) belongs to the language if it is a model of a finite list of EPTDs in the sense given in Guillaume and Perrier (2009). Each node of the list of EPTDs is mapped to a node of the tree model through an interpretation function.…”
Section: Grammars As Constraint Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we apply the Companionship Principle to the Interaction Grammars formalism. We first give a short and simplified description of IG and an example to illustrate them at work; we refer the reader to (Guillaume and Perrier, 2008) for a complete and detailed presentation.…”
Section: Application To Interaction Grammarsmentioning
confidence: 99%
“…Dependencies for TAG were studied in (Joshi and Rambow, 2003). More recently, Marchand et al (2009) showed that it is also possible to extract a dependency structure from a syntactic analysis in Interaction Grammars (IG) (Guillaume and Perrier, 2008).…”
Section: Introductionmentioning
confidence: 99%